Absorptive capacity and performance in Malaysian SMEs / Zarina Denan - Denan, Zarina (Institute of Graduate Studies, UiTM, 2012)
Many small and medium-sized enterprises (SMEs) presently evolve in a complex business environment characterized by globalization the internationalization of markets and the need for greater efficiency effectiveness and competitiveness based on innovation and knowledge. This has put increasing pressure upon the management of these firms especially manufacturing and technological SMEs that must now compete globally. Many entrepreneurial researches have highlighted the significance of potential strategies, technological innovation, or entrepreneurial orientation in improving SMEs productivity.